2004
DOI: 10.1111/j.1439-0531.2004.00500.x
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Intravaginal Applied GnRH‐agonist on the Time of Ovulation and Subsequent Reproductive Performance of Weaned Multiparous Sows

Abstract: In order to prove the effect of 'fixed time insemination' and insemination at standing oestrus after post-weaning application of GnRH, in a Croatian large breeding unit, 502 sows were assigned to three groups and were artificially inseminated (AI) at their first post-weaning oestrus as many times as they stand, in 24-h intervals. The groups were treated as follows: group 1 (control, n = 160) were AI during their standing reflex; group 2 ['GnRH-fixed time insemination' (GnRH-FT-AI), n = 175] were AI, independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Further, other workers have indicated a GnRH‐to‐ovulation interval of 38 h (Langendijk et al. 2000) and 33–34 h (Baer and Bilkei 2004). Taken together, the present data and that in the literature suggest that the ovulation control protocol described herein likely resulted in ovulation consistently at about 38 h after the pLH injection.…”
Section: Discussionmentioning
confidence: 96%
“…Further, other workers have indicated a GnRH‐to‐ovulation interval of 38 h (Langendijk et al. 2000) and 33–34 h (Baer and Bilkei 2004). Taken together, the present data and that in the literature suggest that the ovulation control protocol described herein likely resulted in ovulation consistently at about 38 h after the pLH injection.…”
Section: Discussionmentioning
confidence: 96%
“…approximately 6 h (Pursel et al, 1978;Soede et al, 1995;Weitze et al, 1994), the induction of ovulation before insemination with FT semen seems to be necessary for maximizing in vivo fertility (Huhn and Konig, 1989;Konig et al, 1977). The control of estrus and ovulation with exogenous hormones in gilts and sows has been demonstrated (Baer and Bilkei, 2004;Brussow et al, 1996;Roca et al, 2003;Wiesak et al, 1990). Roca et al (2003) using human chorionic gonadotrophin (hCG) for controlling ovulation reported that 77.5% FR and 9.31 TB were obtained in hormonally treated sow after a single deep AI using a low number of FT spermatozoa.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%
“…Most recently, a gel for intravaginal application of the GnRH analogue triptorelin (OvuGel ® ; Elanco) is being promoted (Baer and Bilkei ; Stewart et al. ).…”
Section: Controlling Oestrus and Time Of Ovulationmentioning
confidence: 99%
“…Most recently, a gel for intravaginal application of the GnRH analogue triptorelin (OvuGel Ò ; Elanco) is being promoted (Baer and Bilkei 2004;Stewart et al 2010). In a study by Knox et al (2011), weaned sows received 100 lg of triptorelin either 96 h post-weaning or at oestrus detection and were subsequently inseminated twice at fixed times.…”
Section: Controlling Oestrus and Time Of Ovulationmentioning
confidence: 99%